Analisis Simulasi Struktur Mesin Penggiling Ketela Menggunakan Sistem Rotary screw Berbasis SolidWorks Simulation - Nazwa Naufal Noviantoro; Rany Puspita Dewi (Journal of Mechanical Engineering and Applied Technology, 2026)
Cassava is one of the important agricultural commodities widely processed into various food products. The grinding process is a crucial stage that affects product quality and production efficiency. However, most small-scale cassava processing industries still utilize conventional grinding equipment with limited capacity and low operational efficiency. Various studies have been conducted to develop cassava processing machines, including slicing, peeling, grating, and grinding machines. Nevertheless, previous research has mainly focused on machine design and performance testing, while structural strength evaluation prior to manufacturing has received limited attention. Therefore, this study aims to analyze the structural characteristics of a cassava grinding machine frame using a rotary screw system through Finite Element Analysis (FEA) based on SolidWorks Simulation. The research was conducted by developing a three-dimensional machine model and performing static structural Simulations using SolidWorks Simulation. The frame material was modeled as alloy steel, while a static load of 1000 N was applied to represent the combined weight of machine components and cassava material during operation. The evaluated parameters included displacement, stress distribution, and factor of safety. The Simulation results showed a maximum displacement of 1.95 mm, indicating that the frame deformation remained relatively small and did not affect machine performance. The maximum stress obtained was 108 MPa, which was significantly lower than the material yield strength of 620 MPa, indicating that the structure operated within the elastic region. In addition, the minimum factor of safety was 5.7, demonstrating that the frame possessed a high level of structural safety under the applied loading conditions. Based on the Simulation results, the designed cassava grinding machine frame using a rotary screw system is structurally safe and feasible for manufacturing because it is capable of withstanding the intended operational loads.